How can we use stem cell-derived cardiomyocytes to understand the involvement of energetic metabolism in alterations of cardiac function? - Rebs, Sabine; Streckfuss-Bömeke, Katrin (Frontiers in Molecular Medicine, 2023)
Mutations in the mitochondrial-DNA or mitochondria related nuclear-encoded-DNA lead to various multisystemic disorders collectively termed mitochondrial diseases. One in three cases of mitochondrial disease affects the heart muscle, which is called mitochondrial cardiomyopathy (MCM) and is associated with hypertrophic, dilated, and noncompact cardiomyopathy. The heart is an organ with high energy demand, and mitochondria occupy 30%–40% of its cardiomyocyte-cell volume. Mitochondrial dysfunction leads to energy depletion and has detrimental effects on cardiac performance. However, disease development and progression in the context of mitochondrial and nuclear DNA mutations, remains incompletely understood. The system of induced pluripotent stem cell (iPSC)-derived cardiomyocytes (CM) is an excellent platform to study MCM since the unique genetic identity to their donors enables a robust recapitulation of the predicted phenotypes in a dish on a patient-specific level. Here, we focus on recent insights into MCM studied by patient-specific iPSC-CM and further discuss research gaps and advances in metabolic maturation of iPSC-CM, which is crucial for the study of mitochondrial dysfunction and to develop novel therapeutic strategies.